Application of cathodoluminescence for on-line monitoring of regime of an industrial electron accelerator - Pomatsalyuk, R.I.; Romanovsky, S.K.; Shevchenko, V.A.; Tenishev, A.Eh.; Titov, V.Yu.; Titov, D.V.; Uvarov, V.L.; Zakharchenko, A.A. (Вопросы атомной науки и техники, 2019)
Continuous monitoring of critical parameters of an industrial electron accelerator provides quality of product processing. For that purpose, the methods of contact-free diagnostics of processing regime are developed. One of them is based on application of a wide-aperture stack-monitor for on-line measurement of beam current, electron energy, and also the mean absorbed dose over the plain of beam scanning in an irradiated object [1]. In the work, the conditions of application of cathodoluminescence (CL), accompanied action of accelerated electrons on amorphous dielectrics, for adjustment of the stack-monitor, and also for measuring in on-line mode the dose in a point of control as well as of distribution of the electron flux density on the surface of the object, is studied. It is shown, that titanium dioxide, keeping the radiation-optical yield at an accumulated dose of up to 4 MGy, can be considered as a promising material for manufacturing of CL detector.